Snoring and nocturnal reflux: association with lung function decline and respiratory symptoms. Issue 2 (28th May 2019) - Emilsson, Össur Ingi; Hägg, Shadi Amid; Lindberg, Eva; Franklin, Karl A.; Toren, Kjell; Benediktsdottir, Bryndis; Aspelund, Thor; Gómez Real, Francisco; Leynaert, Bénédicte; Demoly, Pascal; Sigsgaard, Torben; Perret, Jennifer; et al.
Introduction: The study aim was to examine the association of snoring and nocturnal gastro-oesophageal reflux (nGOR) with respiratory symptoms and lung function, and if snoring and/or nGOR associated with a steeper decline in lung function. Methods: Data from the third visit of the European Community Respiratory Health Survey (ECRHS) was used for cross-sectional analysis. Pre- and post-bronchodilator spirometry was performed, and information on sleep, nGOR and respiratory symptoms was collected (n=5715). Habitual snoring and nGOR were assessed by questionnaire reports. Pre-bronchodilator spirometry from ECRHS I, II and III (20 years follow-up) were used to analyse lung function changes by multivariate regression analysis. Results: Snoring and nGOR were independently associated with a higher prevalence of wheeze, chest tightness, breathlessness, cough and phlegm. The prevalence of any respiratory symptom was 79% in subjects with both snoring and nGOR versus 56% in those with neither (p<0.001). Subjects with both snoring and nGOR had more frequent exacerbations (adjusted prevalence 32% versus 19% among "no snoring, no nGOR", p=0.003). Snoring but not nGOR was associated with a steeper decline in forced expiratory volume in 1 s over 10 years after adjusting for confounding factors (change in % predicted −5.53, versus −4.58 among "no snoring", p=0.04) and forced vital capacity (change in % predicted −1.94, versus −0.99 among "no snoring", p=0.03). Conclusions: Adults reporting both habitual snoring and nGOR had more respiratory symptoms and more frequent exacerbations of these symptoms. Habitual snoring was associated with a steeper decline in lung function over time. Middle-aged adults with habitual snoring have a steeper decline in lung function over 10 years compared to controls. Habitual snorers with nocturnal gastro-oesophageal reflux have a higher prevalence of nocturnal respiratory symptoms than controls. http://ow.ly/YsiK30odcMY